Polyamide composite membrane based on nanobubble-assisted free interface polymerization strategy as well as preparation method and application of polyamide composite membrane

By pre-constructing nanobubbles in aqueous solution and using their upward migration in free interface polymerization process, the stability and capture problems of nanobubbles in the structural regulation of polyamide composite membrane are solved, and the water permeability of the membrane is significantly improved and overall performance.

CN119425424AActive Publication Date: 2025-02-14OCEAN UNIV OF CHINA

Patent Information

Application Number
CN202411729830.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-14
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The prior art has problems in the instability of nanobubble generation, difficulty in trapping by polyamide and disappearance of nanobubble during in-situ interface polymerization, which affects the selectivity and water permeability of the film.

Method used

By introducing nanobubble precursors into aqueous solution, nanobubbles are preconstructed in aqueous solution by relying on the reaction between the precursor and water or the self-decomposition of the precursor, nanobubbles are preconstructed in aqueous solution, and the upward movement of nanobubbles is utilized under the free interface polymerization process. Migration, hierarchical regulation of the structure of the polyamide separation layer, including bottom opening characteristics, internal nanocavity and surface morphological characteristics.

Benefits of technology

The permeable area of ​​the polyamide composite film and the transfer rate of water molecules are significantly improved, the overall performance of the film is improved, the problem of nanobubble disappearance during in-situ interface polymerization is avoided, and the formation of nanocavity structure is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425424A_ABST
    Figure CN119425424A_ABST
Patent Text Reader

Abstract

The invention discloses a polyamide composite membrane based on a nanobubble-assisted free interface polymerization strategy and a preparation method and application of the polyamide composite membrane. Nanobubble precursors of different types and concentrations are loaded in a water-phase solution by a chemical method, and the polyamide composite membrane is prepared by means of reaction between the precursors and water or self-decomposition of the precursors. Nanometer bubbles are pre-constructed in a water phase solution, and under a free interface polymerization process, by utilizing upward migration of the nanometer bubbles at a neutralization phase interface of the water phase solution, hierarchical regulation and control of a polyamide separation layer structure are realized from bottom to top; according to the polyamide composite membrane, the bottom opening characteristic, the internal nano-cavity structure and the surface morphological characteristic of the polyamide separation layer are effectively improved, the transmembrane transmission rate of water molecules is remarkably increased, the hydraulic resistance is reduced, and the water flux of the membrane is remarkably improved on the premise that the salt rejection rate of the polyamide composite membrane is not sacrificed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a polyamide composite membrane based on a nanobubble-assisted free interface polymerization strategy and a preparation method and application thereof, belonging to the technical field of separation membrane preparation and application. Background Art

[0002] Polyamide composite membranes are widely used in water purification, wastewater reuse and seawater desalination. The permeability and selectivity of the membrane are usually determined by the physicochemical properties of the dense polyamide separation layer. Studies have shown that beneath the typical "ridge-valley", strip-shaped, leaf-shaped and other morphologies on the surface of the polyamide separation layer, there may be nanocavity structures that improve the water permeability of the polyamide composite membrane and reduce hydraulic resistance. In recent years, based on in-depth research on reaction heat and by-product acid during interfacial polymerization, researchers have innovatively proposed the concepts of interfacial vaporization and interfacial degassing, providing a reasonable explanation for the formation of nanocavities. The above views have promoted the development of nanobubble strategies to a certain extent and opened up a new path for the design of nanocavities in membranes.

[0003] At present, the generation methods of nanobubbles are generally divided into in-situ reaction and pre-dispersion of nanobubbles in aqueous solution by physical or chemical means, and finally applied to in-situ interfacial polymerization process. Patent CN 110545903B Thin film composite membrane with enhanced membrane permeability of nano-sized bubbles, its preparation method and use, through the reactive additives or soluble gases present in the aqueous solution, or using a nanobubble generator or ultrasound in the aqueous solution to generate nanobubbles, and then through in-situ interfacial polymerization to form a polyamide separation layer containing nanocavities. Patent CN 116920637 B A dense membrane with chemical bubbles that simultaneously improves flux and interception rate and its preparation method, using carbohydrazide as the aqueous phase monomer, using the unique structure of carbohydrazide, reacting under alkaline conditions to release a large number of nanobubbles, and polymerizing with trimesoyl chloride to form a dense polyamide separation layer, so that the polyamide separation layer forms a loose structure rich in nanocavities in the continuously generated bubbles, increasing the effective filtration area of ​​the membrane. However, the in-situ reaction is difficult to ensure the effectiveness of nanobubble generation, and in the transient reaction process of the aqueous phase amine monomer and the organic phase acyl chloride monomer, the nanobubbles formed in situ by the reactive additive may be difficult to be captured by the polyamide, thereby affecting the formation of the nanocavity structure. In addition, under the in-situ interfacial polymerization process, the rapidly released nanobubbles are often restricted by the support layer and cannot escape, and accumulate at the interface, thereby causing strong interface fluctuations, which ultimately affect the cross-linking process and fine structure of the polyamide separation layer and damage its selectivity. The above problems can be effectively avoided by physical means such as pre-pressing soluble gas into the aqueous phase solution, using a bubble generator to generate nanobubbles in the aqueous phase solution, and ultrasonically treating the aqueous phase solution. However, the above method of pre-dispersing nanobubbles in the aqueous phase solution is also affected by the in-situ interfacial polymerization process. During the in-situ interfacial polymerization process, the aqueous phase solution on the surface of the support layer is usually removed by natural drying or roller drying, which may cause a large number of nanobubbles to disappear, thereby weakening its ability to regulate the nanocavity structure in the polyamide separation layer. These problems restrict the development of nanobubbles regulating the structure of polyamide composite membranes. Summary of the invention

[0004] Based on the urgent need to improve the performance of polyamide composite membranes and the limitations of the current nanobubble strategy for regulating the structure of polyamide composite membranes, the present invention proposes a method for preparing polyamide composite membranes based on a nanobubble-assisted free interface polymerization strategy, by introducing a nanobubble precursor into an aqueous solution, relying on the reaction between the precursor and water or the self-decomposition of the precursor (chemical method), pre-constructing nanobubbles in the aqueous solution, and under the free interface polymerization process, using the upward migration of nanobubbles in the aqueous solution and at the interface, adjusting the bottom opening characteristics (opening pore size, opening density, etc.) of the polyamide separation layer, the size and distribution of the internal nanocavities, and the surface morphology characteristics from bottom to top. By controlling these key structural parameters, the overall structure of the polyamide separation layer is optimized, its water permeability area is significantly improved, and the transmission rate of water molecules is enhanced, and finally the performance of the polyamide composite membrane is improved.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] A polyamide composite membrane based on a nanobubble-assisted free interface polymerization strategy, which introduces nanobubble precursors into an aqueous solution, relies on the reaction between the precursor and water or the self-decomposition of the precursor, pre-constructs nanobubbles in the aqueous solution, and utilizes the upward migration of nanobubbles in the aqueous solution and at the interface under the free interface polymerization process to hierarchically regulate the structure of the polyamide separation layer, namely the bottom opening characteristics (opening pore size, opening density), internal nanocavities and surface morphology characteristics. Among them, the average pore size of the bottom opening is 86-183nm, and the opening density is 1.6-7.4 / μm 2 The average lateral size of the nanocavities is 123-212 nm, and the average longitudinal size is 81-125 nm.

[0007] A method for preparing a polyamide composite membrane based on a nanobubble-assisted free interface polymerization strategy specifically comprises the following steps:

[0008] (1) dissolving a polyamine in water to form an aqueous phase solution, wherein the polyamine concentration is 1.0-3.0 wt %; dissolving a polyacyl chloride in an organic solvent to form an organic phase solution, wherein the polyacyl chloride concentration is 0.05-0.2 wt %;

[0009] (2) Adopting a free interfacial polymerization strategy to carry out an interfacial polymerization reaction, first, a porous support layer is placed at the bottom of a reaction container, then, a nanobubble precursor is added to an aqueous solution and ultrasonically treated to pre-construct nanobubbles in the aqueous solution, wherein the concentration of the nanobubble precursor in the aqueous solution is 0.025-1.0 wt %. Subsequently, the ultrasonically treated aqueous solution, an organic buffer solution, and an organic solution are sequentially added to the reaction container to carry out an interfacial polymerization reaction, wherein the reaction container is sequentially composed of a porous support layer, an aqueous solution, an organic buffer solution, and an organic solution from bottom to top, wherein the polyamine in the aqueous solution and the polyacyl chloride in the organic solution migrate to the organic buffer solution to carry out an interfacial polymerization reaction, and at the same time, the nanobubbles in the aqueous solution also migrate upward and are captured during the interfacial polymerization reaction;

[0010] (3) After the polymerization reaction is completed, the remaining solution between the polyamide separation layer and the support layer is extracted through the porous support layer through the outlet at the bottom of the reaction container, so that the prepared polyamide separation layer is deposited on the surface of the polysulfone support layer to form an initial composite membrane. The initial composite membrane is then taken out from the reaction container, cleaned, and heat-treated to form a stable polyamide composite membrane.

[0011] The polyamine and polyacyl chloride in step (1) are raw materials containing amine groups and acyl chlorides for preparing polyamides that are well known to those skilled in the art, and the polyamine includes but is not limited to any one of piperazine, ethylenediamine, hydrazine carbonate, pyridinamine, β-cyclodextrin, 4-aminopiperazine, p-phenylenediamine, o-phenylenediamine, m-phenylenediamine, polyethyleneimine, diethylenetriamine, triethylenetetramine, 1,4-diaminocyclohexane, 3,5-diaminobenzoic acid, 2-aminophenol-4-sulfonamide, bis(2-hydroxyethyl)dimethylammonium chloride, and 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane. or more; polyacid chlorides include but are not limited to phthaloyl chloride, terephthaloyl chloride, trimesoyl chloride, 1,3,5-benzenetrisulfonyl chloride, 1,3,6-naphthalenetrisulfonyl chloride, biphenyl dicarboxylic acid chloride, cyclohexanetricarboxylic acid chloride, trimellitic anhydride chloride, 1,2,4,5-benzenetetracarbonyl chloride, 2,2',4,4'-biphenyltetrachloride, 3,3',5,5'-biphenyltetrachloride, 5-nitrobenzene-1,3-diacid chloride, 5-tert-butyl-1,3-benzene dicarboxylic acid chloride, 5-(1-pyrrolidinyl)-isophthaloyl chloride, and any one or more of 5-sulfonamidoisophthaloyl chloride.

[0012] The porous support layer material in step (2) includes, but is not limited to, any one of polysulfone, polyester, polyethersulfone, polypropylene, polycarbonate, and polyetherimide.

[0013] As an implementation method, in the step (2), the nanobubble precursor reacts with water to form nanobubbles in the aqueous solution, and the nanobubble precursor includes but is not limited to any one or more of sodium borohydride, sodium hydride, calcium hydride, calcium carbide, aluminum carbide, and potassium superoxide. After the nanobubble precursor is added to the aqueous solution, it is immediately subjected to ultrasonic treatment, and the ultrasonic treatment is performed for a total of 2-4 times, each time for 1-6 seconds, to promote the rapid reaction between the precursor and water to generate nanobubbles, that is, to pre-construct nanobubbles in the aqueous solution, thereby regulating the interfacial polymerization reaction, and the ultrasonic power is 200-300W and the frequency is 20-40kHz. The gas types inside the nanobubbles include but are not limited to any one or more of H2, C2H2, CH4, and O2.

[0014] As another implementation, in the step (2), the nanobubble precursor self-decomposes (chemical method) to form nanobubbles in the aqueous solution. In the step (2), the nanobubble precursor includes but is not limited to any one or more of sodium peroxide, calcium peroxide, sodium percarbonate, hydrogen peroxide, ammonium bicarbonate, and sodium bicarbonate. After the nanobubble precursor is added to the aqueous solution, it is immediately subjected to ultrasonic treatment, and the ultrasonic treatment is performed 2-4 times in total, each time for 1-6s, to promote the self-decomposition of the precursor to produce nanobubbles, that is, the interfacial polymerization reaction is regulated by pre-constructing nanobubbles in the aqueous solution, and the ultrasonic power is 200-300W and the frequency is 20-40kHz. The gas types inside the nanobubbles are not limited to any one or two of O2 and CO2.

[0015] The interfacial polymerization reaction time in step (2) is 0.5-5 min, preferably 1-3 min.

[0016] The organic buffer in step (2) is the organic phase in the organic phase solution, including but not limited to any one of toluene, n-pentane, n-hexane, n-heptane, n-octane, n-decane, cyclohexane, and isoparaffin.

[0017] In step (3), the outlet at the bottom of the reaction container is connected to a vacuum pump or an exhaust fan, and the remaining aqueous phase solution is discharged through the outlet at the bottom of the reaction container by the vacuum pump or the exhaust fan, while promoting the deposition of the polyamide separation layer on the surface of the polysulfone support layer.

[0018] In step (3), the height of the aqueous phase solution is 3-6 mm, the height of the organic buffer solution is 0.1-0.2 mm, and the height of the organic phase solution is 2-4 mm.

[0019] In step (3), the heat treatment temperature is 50-90° C. and the time is 1-5 min, which removes the organic solvent remaining on the surface and inside of the polyamide separation layer and promotes further cross-linking between the amine group and the acyl chloride to form a polyamide composite membrane.

[0020] The polyamide composite membrane is used for desalination treatment in a solution.

[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) Compared with the strategy of additionally using an acid etching method to generate nanocavities, the present invention pre-constructs nanobubbles in an aqueous solution by a reaction between a precursor and water or a self-decomposition of a precursor, and uses nanobubbles to construct nanocavities in a polyamide separation layer, thereby avoiding the negative impact of the acid etching process on the physicochemical structure of the separation layer, and is beneficial to ensuring the compactness of the separation layer; (2) Compared with the control strategy of generating nanobubbles by an in-situ chemical reaction in an in-situ interfacial polymerization process, the present invention uses a strategy of pre-constructing nanobubbles before the interfacial reaction, thereby avoiding the problem that the in-situ generated nanobubbles are difficult to be captured by the polyamide separation layer, and ensuring the effectiveness of nanobubbles in regulating the nanocavity structure in the separation layer; (3) Compared with the strategy of pre-dispersing nanobubbles by physical means in an in-situ interfacial polymerization process, the present invention uses a strategy of pre-constructing nanobubbles to assist free interfacial polymerization, thereby effectively avoiding the phenomenon of nanobubbles disappearing due to the drying or rolling of the aqueous solution during the in-situ interfacial polymerization process. , ensuring the regulation of the interfacial polymerization process and the structure of the polyamide separation layer by nanobubbles in the aqueous solution; (4) Compared with the strategy of regulating in situ interfacial polymerization by nanobubbles, the present invention adopts a strategy of regulating free interfacial polymerization by nanobubbles to avoid the adsorption of nanobubbles on the surface of the support layer, and allows the nanobubbles in the aqueous solution and at the interface to migrate freely to the organic solution, thereby achieving hierarchical regulation of the bottom, internal and surface structures of the polyamide separation layer, laying a solid foundation for improving the performance of the polyamide composite membrane; (5) The present invention adds a buffer solution between the aqueous solution and the organic solution to regulate the reaction rate of the interfacial polymerization, avoid the interfacial polymerization reaction being too fast to capture bubbles, and at the same time, the rising of bubbles is conducive to the hierarchical regulation of the polyamide separation layer structure; (6) The nanobubble regulation strategy proposed in the present invention has strong universality and can be widely applied to a variety of precursors that can react with water or can self-decompose to produce nanobubbles, and the strategy can be flexibly applied to a variety of interfacial polymerization systems, with high practical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is Comparative Example 1, which is the surface, cross-section and back SEM images of the polyamide layer prepared without introducing nanobubbles.

[0023] Figure 2 This is Example 2, the surface, cross-section and back SEM images of the polyamide layer prepared based on the H2 nanobubble regulation strategy.

[0024] Figure 3 Surface SEM images of polyamide layers prepared based on H2 nanobubble control strategies with different concentrations in Examples 1, 3, and 4.

[0025] Figure 4 This is Example 5, the surface, cross-section and back SEM images of the polyamide layer prepared based on the O2 nanobubble regulation strategy.

[0026] Figure 5 This is Example 6, the surface, cross-section and back SEM images of the polyamide layer prepared based on the CO2 nanobubble regulation strategy. DETAILED DESCRIPTION

[0027] The present invention provides a method for preparing a polyamide composite membrane based on a nanobubble-assisted free interface polymerization strategy, wherein nanobubbles are pre-constructed in the aqueous solution by introducing a nanobubble precursor into the aqueous solution, relying on the reaction between the precursor and water or the self-decomposition of the precursor. Under the free interface polymerization process, the overall structure of the polyamide separation layer is hierarchically regulated by utilizing the upward migration of nanobubbles in the aqueous solution and at the interface, thereby significantly improving the performance of the polyamide composite membrane. The technical solution will be described in detail below through examples and drawings. Obviously, the described embodiments are only some embodiments of the present invention and do not represent all embodiments.

[0028] Comparative Example 1:

[0029] A method for preparing a polyamide reverse osmosis membrane under a free interface polymerization process, specifically comprising:

[0030] First, a polysulfone support layer is placed at the bottom of a reaction container (with a radius of 40 mm), and an aqueous solution containing 2.0 wt% of m-phenylenediamine is poured into the reaction container, and the height of the aqueous solution is about 3 mm; then, 0.5 mL of n-hexane buffer solution (with a height of about 0.1 mm) and an organic solution containing 0.1 wt% of trimesoyl chloride are added to the surface of the aqueous solution in sequence, and the height of the organic solution is about 2 mm; the reaction is carried out for about 3 minutes, and a vacuum pump is connected to the bottom outlet of the reaction container, and the reaction container is filtered by the vacuum pump, and the solution between the polysulfone support layer and the polyamide separation layer is extracted through the polysulfone support layer, so that the prepared polyamide separation layer is deposited on the surface of the polysulfone support layer; finally, the prepared composite reverse osmosis membrane is taken out by pulling, rinsed with n-hexane, and transferred to an oven at 80°C for heat treatment for 3 minutes.

[0031] Embodiment 1:

[0032] A method for preparing a polyamide reverse osmosis membrane based on a H2 nanobubble control strategy under a free interface polymerization process is as follows:

[0033] First, a polysulfone support layer was placed at the bottom of a reaction vessel (radius of 40 mm), 0.025 wt% sodium borohydride was added to an aqueous solution containing 2.0 wt% m-phenylenediamine, and ultrasound was applied 3 times for 2 s each time to promote a violent reaction between sodium borohydride and water, thereby quickly generating H2 nanobubbles. The ultrasonic power was 300 W and the frequency was 40 kHz. Subsequently, an aqueous solution containing nanobubbles and m-phenylenediamine was poured into the reaction vessel, and the height of the aqueous solution was about 3 mm. The subsequent experimental steps and conditions were the same as those in Comparative Example 1.

[0034] Embodiment 2-4:

[0035] The concentrations of sodium borohydride were 0.05 wt %, 0.075 wt % and 0.1 wt % respectively, and the other experimental conditions were the same as those in Example 1.

[0036] Comparative Example 2:

[0037] Compared with Example 1, the aqueous phase solution of this comparative example was not added with sodium borohydride and only subjected to ultrasonic treatment, while other aspects were the same.

[0038] Comparative Example 3:

[0039] Compared with Example 1, only 0.05 wt % sodium borohydride was added to the aqueous solution of this comparative example without ultrasonic treatment, and the other aspects were the same.

[0040] Embodiment 5:

[0041] A method for preparing a polyamide reverse osmosis membrane based on an O2 nanobubble control strategy under a free interface polymerization process is as follows:

[0042] 0.05 wt % sodium percarbonate was added to an aqueous solution containing 2.0 wt % m-phenylenediamine, and ultrasound was applied 3 times for 2 s each time to promote the self-decomposition of sodium percarbonate, thereby generating O2 nanobubbles. The ultrasonic power was 300 W and the frequency was 40 kHz. The subsequent experimental steps and conditions were the same as those in Example 1.

[0043] Embodiment 6:

[0044] A method for preparing a polyamide reverse osmosis membrane based on a CO2 nanobubble control strategy under a free interface polymerization process is as follows:

[0045] 0.46 wt % sodium bicarbonate was added to the aqueous solution containing 2.0 wt % m-phenylenediamine, and ultrasound was applied 3 times for 2 s each time to promote the self-decomposition of sodium bicarbonate to generate CO2 nanobubbles. The ultrasonic power was 300 W and the frequency was 40 kHz. The subsequent experimental steps and conditions were the same as those in Example 1.

[0046] Comparative Example 4:

[0047] Compared with Example 6, only 0.46 wt % of sodium bicarbonate was added to the aqueous solution of this comparative example without ultrasonic treatment, and the other aspects were the same.

[0048] Test Example 1:

[0049] The performance test process of polyamide reverse osmosis membrane is as follows:

[0050] The water flux and salt rejection of the reverse osmosis membrane were tested in a cross-flow filtration device. The test conditions were: the feed liquid was 2000ppm sodium chloride solution, the operating temperature was 25℃, the pressure was 2MPa, and the effective filtration area of ​​the membrane was 12.56cm 2 , run for at least 1h to keep the water flux stable.

[0051] Table 1 is a data table of water flux and salt rejection of polyamide reverse osmosis membrane prepared based on H2, O2 or CO2 nanobubbles under free interface polymerization process. In the process of regulating the structure of polyamide separation layer by using H2 nanobubbles, as the concentration of sodium borohydride increases, the size of H2 nanobubbles increases accordingly. This increase in size not only leads to the continuous expansion of the size of the nanocavity in the polyamide separation layer, but also promotes the continuous increase in the apparent thickness of the separation layer. In theory, the enlarged nanocavity is conducive to improving the effective permeable area of ​​the polyamide separation layer, and reducing the transmission resistance of water molecules, and finally inducing the improvement of water flux. However, the performance test results of Comparative Example 1 and Examples 1-4 show that the salt rejection of several reverse osmosis membranes is relatively small, and the water flux shows a trend of increasing first and then decreasing, wherein Example 2 shows the highest water flux. This result may be related to the change in the thickness of the polyamide separation layer, and the continuously enlarged nanocavity causes the apparent thickness of the polyamide separation layer to increase excessively, thereby weakening the advantages brought by the nanocavity to a certain extent. The above results indicate that the best membrane performance can be obtained by adjusting the nanobubble precursor concentration and coordinating the changes between the nanocavity size and the thickness of the polyamide separation layer.

[0052] The nanobubble-regulated free interface polymerization strategy proposed in the present invention has a certain universality. By adjusting the way the precursor produces nanobubbles, that is, using its self-decomposition to pre-construct nanobubbles in the aqueous solution, the structure and performance of the reverse osmosis membrane can also be improved. In Examples 5 and 6, by replacing the nanobubble precursors with sodium percarbonate and sodium bicarbonate, the water flux of the reverse osmosis membrane prepared thereby shows different degrees of improvement, and retains a relatively reasonable salt rejection rate. The performance of Comparative Example 2, which was only subjected to ultrasonic treatment, was close to that of Comparative Example 1. This was mainly because it was difficult to generate a large number of nanobubbles in the aqueous solution to regulate the structure of the polyamide layer (the opening density and pore size at the bottom of the polyamide layer, and the size of the nanocavities inside the polyamide layer) by relying solely on ultrasound. The water flux of Comparative Example 3, which added sodium borohydride but was not subjected to ultrasonic treatment, was greatly improved, but the salt interception rate was significantly reduced. This was because the violent reaction between sodium borohydride and the aqueous solution produced a large number of large H2 bubbles, forming large and unevenly distributed nanocavities while increasing the thickness of the polyamide layer, destroying the stability of the interfacial polymerization process, thereby damaging the compactness of the polyamide separation layer. It can be found that ultrasound can eliminate large bubbles, increase the bubble generation rate and bubble uniformity. The results of Comparative Examples 2 and 3 show that only ultrasonic treatment of the aqueous solution, or only introduction of a sodium borohydride precursor, cannot effectively regulate the structure and performance of the polyamide composite membrane. In Comparative Example 4, only sodium bicarbonate was added to the aqueous phase solution without ultrasonic treatment. Compared with Example 6, the water flux of the corresponding membrane was reduced and the salt rejection rate was slightly reduced. Sodium bicarbonate self-decomposed in the aqueous phase to produce carbon dioxide bubbles slowly, and ultrasound could accelerate the generation of bubbles. Omitting ultrasound affected the structure of the separation layer and reduced the overall separation performance. Compared with Comparative Example 1, the water flux was improved and the salt rejection rate was not much different. This was mainly attributed to the reaction between the interfacial polymerization by-product acid and the undecomposed sodium bicarbonate. The nanobubbles generated in situ effectively regulated the overall structure of the polyamide layer, which can also be confirmed from the average density of the bottom openings of the reverse osmosis membrane and the size of the nanocavities in Table 2.

[0053] Table 1 Water flux and salt rejection of reverse osmosis membranes prepared in Comparative Examples 1-4 and Examples 1-6

[0054]

[0055]

[0056] Figure 1 It is shown that the surface of the polyamide reverse osmosis membrane in Comparative Example 1 presents a ring-shaped structure, there are fewer nanocavities in the membrane, and a large number of incompletely opened pores are scattered on the back of the membrane. Figure 2 a and Figure 3The surface morphology characteristics of the membranes of Examples 1-4 show that with the increase in the concentration of the H2 nanobubble precursor, it can be seen that the membrane surface evolves from rough to smooth and then to a bubble ring structure. Among them, the smooth surface of the H2-0.05% membrane is mainly attributed to the high heat dissipation rate of the free interface polymerization process and the appropriate amount of nanobubbles produced by the precursor concentration, which provides a template for the growth of polyamide prepolymers, thereby enhancing the interfacial stability during the interfacial polymerization process. Thereafter, as the concentration of the H2 nanobubble precursor increases to 0.075wt%, the nanobubble content in the aqueous solution increases accordingly, which leads to an increase in the content of nanobubbles migrating into the organic solution. During the cross-interface transmission of nanobubbles from bottom to top, a bubble ring structure is finally formed on the surface of the polyamide separation layer. When the precursor concentration is further increased to 0.1wt%, the size of the bubble rings on the membrane surface increases significantly. An in-depth analysis of Example 2 is shown below. Figure 2 As shown in Figures b and c, it can be seen from the figure that there are obvious nanocavity structures dispersed inside the H2-0.05% membrane. Compared with Comparative Example 1, the aperture and opening density of the back openings of the H2-0.05% membrane are significantly increased. The introduction of H2 nanobubbles effectively improves the bottom opening characteristics of the polyamide separation layer, optimizes the internal nanocavity size and distribution, and promotes the transmembrane transmission rate of water molecules under the synergistic effect of the two, thereby enhancing the performance of the reverse osmosis membrane.

[0057] Figure 4 a and 5a are the surface morphologies of the reverse osmosis membranes in Examples 5 and 6, respectively. It can be seen that the presence of O2 and CO2 nanobubbles promotes the formation of bubble rings or smooth membrane surfaces. From the above analysis, it can be seen that slight changes in the concentration of nanobubbles have a significant effect on the membrane surface morphology. Therefore, the difference in the surface morphology of the O2 and CO2 membranes may be attributed to the different nanobubble contents produced by the self-decomposition of the two precursors. Compared with Comparative Example 1, the polyamide separation layer regulated by O2 and CO2 nanobubbles is dispersed with obvious nanocavities, and the aperture of the back opening is significantly increased.

[0058] Table 2 Structural parameters of the polyamide separation layers prepared in Comparative Examples 1-4 and Examples 1-6

[0059]

[0060] The above results indicate that by adding nanobubble precursors to the aqueous solution, pre-constructing nanobubbles by the reaction between the precursor and water or the self-decomposition of the precursor, and utilizing the migration of nanobubbles from the aqueous phase to the organic phase solution, the bottom opening characteristics, internal nanocavity structure, and surface morphology characteristics of the polyamide separation layer can be hierarchically regulated, thereby effectively improving the performance of the polyamide composite membrane.

Claims

1. A polyamide composite membrane based on nanobubble-assisted free interface polymerization strategy, characterized in that: By introducing nanobubble precursors into the aqueous solution, nanobubbles are pre-constructed in the aqueous solution by relying on the reaction between the precursor and water or the self-decomposition of the precursor. Under the free interface polymerization process, the upward migration of nanobubbles in the aqueous solution and at the phase interface is utilized to hierarchically regulate the structure of the polyamide separation layer.

2. The polyamide composite membrane based on nanobubble-assisted free interface polymerization strategy according to claim 1, characterized in that: The polyamide separation layer forms a bottom opening layer and an internal nanocavity layer, wherein the average pore size of the bottom opening is 86-183nm and the average density is 1.6-7.4 / μm 2 The average lateral size of the nanocavity is 123-212 nm, the average longitudinal size is 81-125 nm, and the average thickness of the polyamide separation layer is 168 nm-346 nm.

3. A method for preparing a polyamide composite membrane using a nanobubble-assisted free interface polymerization strategy, characterized in that: The following steps are involved: (1) dissolving a polyamine in water to form an aqueous phase solution, wherein the polyamine concentration is 1.0-3.0 wt %; dissolving a polyacyl chloride in an organic solvent to form an organic phase solution, wherein the polyacyl chloride concentration is 0.05-0.2 wt %; (2) using a free interfacial polymerization strategy to carry out an interfacial polymerization reaction, first, placing a porous support layer at the bottom of a reaction container, then adding a nanobubble precursor to an aqueous solution and ultrasonically treating it, pre-constructing nanobubbles in the aqueous solution, wherein the concentration of the nanobubble precursor in the aqueous solution is 0.025-1.0 wt %, and then, sequentially adding the ultrasonically treated aqueous solution, an organic buffer solution, and an organic phase solution to the reaction container for an interfacial polymerization reaction, wherein the reaction container is sequentially composed of a porous support layer, an aqueous solution, an organic buffer solution, and an organic phase solution from bottom to top; (3) After the polymerization reaction is completed, the remaining solution between the polyamide separation layer and the support layer is extracted through the porous support layer through the outlet at the bottom of the reaction container, so that the prepared polyamide separation layer is deposited on the surface of the polysulfone support layer to form an initial composite membrane. The initial composite membrane is then taken out from the reaction container, cleaned, and heat-treated to form a stable polyamide composite membrane.

4. The method for preparing a polyamide composite membrane based on nanobubble-assisted free interface polymerization strategy according to claim 3, characterized in that: The polyamine is any one or more of piperazine, ethylenediamine, hydrazine carbonate, pyridinamine, β-cyclodextrin, 4-aminopiperazine, p-phenylenediamine, o-phenylenediamine, m-phenylenediamine, polyethyleneimine, diethylenetriamine, triethylenetetramine, 1,4-diaminocyclohexane, 3,5-diaminobenzoic acid, 2-aminophenol-4-sulfonamide, bis(2-hydroxyethyl)dimethylammonium chloride, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane; the polyacyl chloride is any one or more of phthaloyl chloride, terephthaloyl chloride, Any one or more of benzene trimethylene dicarboxylic acid chloride, 1,3,5-benzenetrisulfonyl chloride, 1,3,6-naphthalenetrisulfonyl chloride, biphenyl dicarboxylic acid chloride, cyclohexane trimethylene dicarboxylic acid chloride, trimellitic anhydride chloride, 1,2,4,5-benzene tetracarbonyl chloride, 2,2',4,4'-biphenyl tetrachloride, 3,3',5,5'-biphenyl tetrachloride, 5-nitrobenzene-1,3-diacyl chloride, 5-tert-butyl-1,3-benzene dicarboxylic acid chloride, 5-(1-pyrrolidinyl)-isophthaloyl chloride, and 5-sulfonamidoisophthaloyl chloride.

5. The method for preparing a polyamide composite membrane based on nanobubble-assisted free interface polymerization strategy according to claim 3, characterized in that: The porous support layer material is any one of polysulfone, polyester, polyethersulfone, polypropylene, polycarbonate and polyetherimide.

6. The method for preparing a polyamide composite membrane based on nanobubble-assisted free interface polymerization strategy according to claim 3, characterized in that: In the step (2), the nanobubble precursor reacts with water to form nanobubbles in the aqueous solution, or in the step (2), the nanobubble precursor self-decomposes to form nanobubbles in the aqueous solution.

7. The method for preparing a polyamide composite membrane based on nanobubble-assisted free interface polymerization strategy according to claim 6, characterized in that: The nanobubble precursor is any one or more of sodium borohydride, sodium hydride, calcium hydride, calcium carbide, aluminum carbide, potassium superoxide, sodium peroxide, calcium peroxide, sodium percarbonate, hydrogen peroxide, ammonium bicarbonate, and sodium bicarbonate.

8. The method for preparing a polyamide composite membrane based on nanobubble-assisted free interface polymerization strategy according to claim 7, characterized in that: After the nanobubble precursor is added into the aqueous solution, ultrasonic treatment is immediately performed for 2-4 times, each time for 1-6 seconds, with an ultrasonic power of 200-300 W and a frequency of 20-40 kHz.

9. The method for preparing a polyamide composite membrane based on nanobubble-assisted free interface polymerization strategy according to claim 3, characterized in that: In step (2), the height of the aqueous phase solution is 3-6 mm, the height of the organic buffer solution is 0.1-0.2 mm, and the height of the organic phase solution is 2-4 mm.

10. Use of the polyamide composite membrane according to claim 1, or the polyamide composite membrane prepared by the method according to any one of claims 1 to 9 in a solution desalination process.

Citation Information

Patent Citations

  • Thin-film composite membranes with enhanced membrane permeability containing nano-sized bubbles, their preparation methods and applications

    CN110545903B

  • A dense membrane for simultaneously improving flux and interception rate by chemical bubbles and preparation method thereof

    CN116920637B

  • Method for producing nanoscale bubbles and device of method

    CN110152511A

  • Polyamide composite membrane prepared by using inorganic salt additive, and preparation and application thereof

    CN110394069A

  • Thin film composite membrane with nano-sized bubbles having enhanced membrane permeability, preparation methods and uses thereof

    CN110545903A

Cited By

  • Nano-bubble induced amphiphilic compound self-assembled polyamide composite membrane as well as preparation method and application of nano-bubble induced amphiphilic compound self-assembled polyamide composite membrane

    CN120984124A

  • Household high-flux high-desalination reverse osmosis composite membrane based on thick desalination layer design and preparation method thereof

    CN122499659A

  • Nano-bubble auxiliary reverse osmosis membrane and preparation method thereof

    CN122499672A